2009
DOI: 10.2147/ndt.s4720
|View full text |Cite
|
Sign up to set email alerts
|

Adult ADHD and comorbid depression: A consensus-derived diagnostic algorithm for ADHD

Abstract: Objective: Many patients present to their physician with depression as their primary symptom. However, depression may mask other comorbid disorders. This article presents diagnostic criteria and treatment recommendations (and monitoring) pertaining to the diagnosis of adult attention defi cit hyperactivity disorder (ADHD), which may be missed in patients who present with depressive symptoms, or major depressive disorder (MDD). Other co-occurring conditions such as anxiety, substance use, and bipolar disorder a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 76 publications
1
17
0
Order By: Relevance
“… 8 , 21 When ADHD was accompanied by depression, the patients were afflicted with worsened conditions, which subsequently impinged on their QOL. 22 The results of this study are consistent with previous studies that determined ADHD symptoms significantly increased the severity of depression.…”
Section: Discussionsupporting
confidence: 92%
“… 8 , 21 When ADHD was accompanied by depression, the patients were afflicted with worsened conditions, which subsequently impinged on their QOL. 22 The results of this study are consistent with previous studies that determined ADHD symptoms significantly increased the severity of depression.…”
Section: Discussionsupporting
confidence: 92%
“…For example, most individuals with depression experience psychiatric comorbidity, according to the National Comorbidity Survey Replication. 145 , 146 It has been reported that depression occurs in 9%–50% of patients with ADHD, 147 and STAR*D study has reported that approximately a third of patients with MDD also have a substance use disorder. When MDD is comorbid with ADHD, it is associated with a much more severe course, an earlier age of illness onset, more complex psychiatric comorbidities, decreased quality of life, greater burden of illness, greater illness complexity, lower social functioning, lower work productivity, and lower employment rates than patients with MDD alone.…”
Section: Hedonic Tone and Mood Disordersmentioning
confidence: 99%
“…Attention Deficit Hyperactivity Disorder (ADHD) is a common neurobehavioral disorder that is characterized by inattention, hyperactivity and impulsivity. It is associated with considerable social, family, behavioral and cognitive dysfunction and is comorbid with depression, bipolar disorder, anxiety, and substance use [1] . ADHD in adults is often left untreated and significantly correlates with previous married status, unemployment, and European ancestry [2] .…”
Section: Introductionmentioning
confidence: 99%